Appreciative Inquiry: An approach for learning and change based on our own best practices? - Acosta, Anne; Douthwaite, Boru (Institute of Learning, 2005)
Since it was conceptualized in the late 1980s as a research methodolog y and change paradigm, the technique of ‘appreciative inquiry’ (AI) ha s proved to be highly effective for capturing the positive features of an organization or social system and energizing the members to strive for higher levels of performance. This Brief outlines the basic princ iples and methods of AI, describes various domains in which it has bee n undertaken and provides a recent example of its use in a centre affi liated with the Consultative Group on International Agricultural Resea rch (CGIAR).